A Quick-and-Dirty Method for Assessing the Risk of Negative Aeration Effects of Shock Absorbers Equipped with Shim Sliding Base Valves - Czop, Piotr; Gniłka, Jacek (Computer Assisted Methods in Engineering and Science, 2022)
This paper presents a quick-and-dirty method to assess the risk of negative aeration effects occurring in twin-tube hydraulic shock absorbers used in passenger cars at the early design stage. The method is intended to be implemented as an engineering calculation tool based on the computational fluid dynamics (CFD) two-dimensional (2D)/three-dimensional (3D) steady-state single-phase model. The CFD model was previously validated with the use of the particle image velocimetry (PIV) experiment. The negative aeration effect is a wellknown issue for automotive and railway shock absorbers manufacturers. It results in uncontrolled on-vehicle vibrations and the deteriorated shock absorber damping characteristic. The major aeration contributor in twin-tube hydraulic shock absorbers is the sliding shim intake valve, which requires design optimization to avoid a negative aeration effect. The method validation was conducted with the customized test rig equipped with a transparent cylinder where the specific sliding intake valve was assembled. The proposed method also requires a lumped-parameter model of a twin-tube shock absorber, which allows to simulate boundary conditions in assessing particular reservoirs of a shock absorber, i.e., pressures and flow balance. The method is implemented as a calculation routine that converts CFD pressure regions into a gas concentration indicator (GCI) using the pressure-density characteristic of an oil-gas emulsion of a shock absorber. GCI is calculated based on the sum of particular 2D/3D grid elements. The method application is to minimize the risk of occurrence of negative aeration effects by avoiding expensive and time-consuming experimental tests. This method can also be used for in-production shock absorbers projects as a part of a continuous improvement cycle or in the case of inefficient shock absorbers claimed by a vehicle manufacturer. The application scope of the method can be extended for arbitrary twin-tube designs of shock absorbers in the automotive and railway industries.